Interferometry Recent Developments and Contemporary Applications - Bhowmick, Mithun; Ullrich, Bruno (IntechOpen, 2019)
The authors provide an overview of recent developments in the field of interferometry. To achieve this aim, a broad range of topics is presented by experts who have summarized recent results drawn from theory and experiments. The simplicity and versatility of interferometry technique can be easily seen in the broad range of problems discussed in the text. This important book project presents recent, unique updates on interferometry.